Complications and Prevention of Anemia during Pregnancy - Usmonova Zarina Muxtor qizi, (Journal of Science in Medicine and Life, 2024)
Bleeding during pregnancy is an obstetric complication in which bloody fistulas of varying amounts (from small to massive) are released from the vagina. Female genitals - vagina, cervix; emerging or already formed utero-placental and feto-placental complex. Bleeding during early pregnancy is often associated with the threat of termination. Under the influence of the influencing factor, the contractile activity of the uterus increases, which leads to the separation of part of the chorion (placenta) tissue. This process is accompanied by the rupture of blood vessels that naturally bleed and release.